Novel Variants of the Human Flavin-Containing Monooxygenase 3 (FMO3) Gene Associated with Trimethylaminuria - Motika, Meike S. (2009)
The disorder trimethylaminuria (TMAu) often manifests itself in a body odor for individuals affected. TMAu is due to decreased metabolism of dietary-derived trimethylamine (TMA). In a healthy individual, 95% or more of TMA is converted by the flavin-containing monooxygenase 3 (FMO3, EC 1.14.13.8) to non-odorous trimethylamine N-oxide (TMA N-oxide). Several single nucleotide polymorphisms (SNPs) of the FMO3 gene have been described and result in an enzyme with decreased or abolished functional activity for TMA N-oxygenation thus leading to TMAu. Herein, we report two novel mutations observed from phenotyping and genotyping two self-reporting individuals. Sequence analysis of the exon regions of the FMO3 gene of a young woman with severe TMAu revealed heterozygous mutations at positions 187 (V187A), 158 (E158K), 308 (E308G), and 305 (E305X). Familial genetic analysis showed that the E158K/V187A/E308G derived from the same allele from the mother, and the E305X was derived from the father. FMO3 variants V187A and V187A/E158K were characterized for oxygenation of several common FMO3 substrates (i.e., 5- and 8-DPT, mercaptoimidazole (MMI), TMA, and sulindac sulfide) and for its thermal stability. Our findings show that with the combination of V187A/E158K mutations in FMO3, the enzyme activity is severely affected and possibly contributes to the TMAu observed. In another study, genotyping analysis of a 17 year old female revealed a mutation that caused a frame shift after K415 and resulted in a protein variant with only 486 amino acid residues that was associated with severe TMAu.